Biochar for environmental sustainability in the energy-water-agroecosystem nexus. (October 2021) - Malyan, Sandeep K.; Kumar, Smita S.; Fagodiya, Ram Kishor; Ghosh, Pooja; Kumar, Amit; Singh, Rajesh; Singh, Lakhveer
Abstract: Global warming, management of soil health, remediation of contaminated wastewater, and sustainable alternate source of energy are the major challenges of the 21st century. Biochar has an enormous potential in addressing these global issues and can act as a catalyst in achieving sustainable development goals (SDGs). Biochar produced from waste biomass (crop residues, algal biomass, municipal waste, etc.) has dual advantages of waste management along with its application in different sectors. The mineral contents and buffering capacity of biochar make it an ultimate catalyst for anaerobic digestion which significantly enhances bioenergy production. Supplementing anaerobic digestion with biochar can increase biogas and biological hydrogen production up to 57% and 118% respectively, over control. Biochar addition to soil improves soil health, porosity and aeration which mitigates greenhouse gas emission from soil. Addition of biochar at the optimum level in rice can reduce cumulative methane emission up to 60%. In this manuscript, the potential of biochar for bioenergy production (biogas and biological hydrogen production), greenhouse gases mitigation, carbon sequestration in soils, and waste water remediation is discussed in detail along with the challenges and future prospects of biochar. This review identifies the key issues which need to be addressed for sustainable utilization of biochar. Graphical abstract: Image 1 Highlights: Biochar is nutrient rich biomass and its use is economic and environment friendly. Biochar enhances biogas and bio-hydrogen production in anaerobic reactors. Biochar based MFCs are economically and environmentally sustainable. Biochar addition in soil sequesters carbon and reduces CH4 and N2 O emissions. Biochar use potentially removes several emerging contaminants from wastewater.